Development Of The Ogoh-Ogoh Parade From A Religious Ritual To A Tourist Attraction In Bali - Prianta, Putu Agung; Sulistyawati, Anastasia (Politeknik Internasional Bali, 2024)
The Ogoh-ogoh parade has become one of the events in the Hindu religious rituals to welcome Nyepi Day. Its initial development from a cultural element transformed into a religious ritual and further commodified into a tourist attraction. The research aims to explore the historical development of the Ogoh-ogoh parade in the context of religion and tourism and to understand the impact of the Ogoh-ogoh parade's transformation on the cultural identity and religious practices of the Balinese community. The theories employed include cultural transformation, cultural commodification, and cultural change. A qualitative method with data collection through literature study was used. The research findings reveal various histories of Ogoh-ogoh: the pitra yadnya (Sang Kalika), the Barong Landung, the boredom of statue craftsmen, the Ngusaba Ndong-Nding, and the adaptation of scarecrow. It became a tourist object because Ogoh-ogoh is not mentioned in Hindu scriptures or sacred texts. The impacts of the parade as a tourist attraction include changes in interpersonal community relationships, an increase in anomalies, cultural identity and religious rituals, and an increase in tourist visits. This study is expected to provide new insights into how the religious community and the Balinese society in general respond to the pressures of modernization and globalization.